2020
DOI: 10.3390/su12093804
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Climate Change and Regional Planning: A Scrutiny of Sectoral Instruments

Abstract: Adaptation to climate change means adjustment of human and natural systems to climatic actual or expected events, in order to minimize damage or maximize benefit. Adaptation implies involvement, coordination, and cooperation of different actors and sectors. Multi-actor collaboration usually characterizes the drafting of regional plans, which act as bridges between national and local administrative levels. Regional administrations address resilience issues, through spatial planning processes. This study focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Using Scopus and Web of Science databases, the search query returned a total of 200 documents (at the time this research was conducted), which were then run through a screening and selection process (phase II). This process consisted of the development of specific criteria to scrutinize the papers and, thus, select only the relevant ones [66,73]. The titles, abstracts, and the full text of the resulting sample were screened for relevance according to the criteria presented in Table 1: (1) conceptual and empirical studies on green infrastructure planning practices; (2) inclusion of explicit or implicit green infrastructure planning principles.…”
Section: Methodsmentioning
confidence: 99%
“…Using Scopus and Web of Science databases, the search query returned a total of 200 documents (at the time this research was conducted), which were then run through a screening and selection process (phase II). This process consisted of the development of specific criteria to scrutinize the papers and, thus, select only the relevant ones [66,73]. The titles, abstracts, and the full text of the resulting sample were screened for relevance according to the criteria presented in Table 1: (1) conceptual and empirical studies on green infrastructure planning practices; (2) inclusion of explicit or implicit green infrastructure planning principles.…”
Section: Methodsmentioning
confidence: 99%
“…Petzold et al studied the role of indigenous knowledge on climate change adaptation through a global evidence map of academic literature, and their results showed that there are adaptation knowledge gaps in northern and central Africa, South America, northern Asia, Australia, and urban areas [35]. Ledda et al found out that the current climate adaptation plan in many regions could not fully work because of failing to include key adaptation sectors and actions [36]. To design effective regional climate adaptation plan, decision-makers need a state-of-the-art, regional, and sector-specific knowledge [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Possibility of joint measures within similar legal structures/exchange of expertise on entry points for consideration of climate change adaptation [26] Non-harmonised or non-binding planning frameworks or strategies may impede integrative climate proofing [57], as well as lacking or diverging levels of detail within specific planning instruments [26], [59]…”
Section: Legal Framework / Instrumentsmentioning
confidence: 99%
“…Shared cost burden, at least for parts of the risk assessment and adaptation process [48]; Possibility for efficient use of human and financial resources as well as space (in the case of multi-functional measures) [26] Uncertainties/ambiguities regarding cost sharing [48] and limited financial resources [59]; Different internal structures, hierarchies and responsibilities; Asymmetries in political commitment and cultures between different partners may impede uptake of administrative processes [57] This case study area approaches vertical and horizontal cooperation for climate proofing despite very heterogenic planning systems and institutional capacities through cooperation in the PGO. This creates a novel opportunity to develop and discuss a new, integrative planning framework for climate proofing across sectors, planning areas and policy levels that integrates this knowledge on potential barriers in order to enable planners to adequately address them early in the process.…”
Section: Resourcesmentioning
confidence: 99%